THE QUALITY OF EARLY CHILDHOOD EDUCATION SERVICE IN INDONESIA - Sanny, Lim (Bina Nusantara University, 2017)
Education is the most important thing as education is a strategic tool to improve the standard of human life. Parents play a very important role in choosing their children’s school. This research aims to find out the effect of quality of educational service and school reputation to parents’ satisfaction towards parents’ decision in choosing the school. Research is done in Indonesia, taking 400 random samples from Indonesia’s big cities. The result shows that parents’ decision in choosing a school is highly affected by the service quality of educational service and school reputation. As a result, the improvement of service quality for every school is required in order to make parents more satisfied and to gain a good reputation.